Effectiveness of Mindfulness-Based Psychotherapy on Functional Flexibility and Health Hardiness in Patients with Coronavirus Anxiety during the Epidemic - Bakhshandeh Amnieh, Tahereh; Raeisi, Zohreh; Ranjbarkohan, Zohre; Khoshakhlagh, Hassan (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to examine the effectiveness of mindfulness-based psychotherapy on functional flexibility and health hardiness in patients with coronavirus anxiety during the epidemic. Methods: This research utilized a quasi-experimental method with a pre-test, post-test design, including a control group and a three-month follow-up period. The statistical population comprised individuals with coronavirus anxiety who contacted counseling centers in Isfahan for telephone consultations during the summer of 2021. From this population, 33 individuals were selected through purposive sampling and randomly assigned to experimental and control groups. Participants in the experimental group received mindfulness-based psychotherapy (8 sessions) based on Kabat-Zinn’s protocol (2003) over two months. The questionnaires used in this study included the Functional Flexibility Questionnaire (Dennis & Vander Wal, 2010), the Health Hardiness Questionnaire (Gibbhardt, VanderDerf, & Powell, 2001), and the Coronavirus Anxiety Questionnaire (Alipour et al., 2019). Data were analyzed using mixed ANOVA with SPSS23 statistical software. Findings: The results indicated that mindfulness-based psychotherapy significantly impacted functional flexibility (P<0.0001; Eta=0.62; F=52.32) and health hardiness (P<0.0001; Eta=0.65; F=55.09) in patients with coronavirus anxiety. Conclusion: Based on the findings of the present study, mindfulness-based psychotherapy, utilizing techniques such as mindful attitude, mindful activities, addressing problematic emotions, and breathing exercises, can be effectively used to improve functional flexibility and health hardiness in patients with coronavirus anxiety.